A Critical Evaluation Of The Installation Equipment Of In-Stope Rock Bolts And The Effectiveness Thereof In The Merensky Stoping Areas - G. M. J. van Heerden (The Southern African Institute of Mining and Metallurgy, 2002)
Paper written on project work carried out in partial fulfilment of B. Eng (Mining Engineering) degree The Union Section of Anglo Platinum is situated ±18 km west of the town of Northam on the north-western rim of the Bushveld Igneous Complex. Both the Merensky and UG2 reefs are mined. Support of the Merensky stoping areas with rock bolts is specifically problematic due to the stoping width restrictions varying around 90 cm. The installation equipment of in-stope rock bolts and the effectiveness thereof in the Merensky stoping areas was critically evaluated. In order to do this a background research on the need for better on-the-face support had to be conducted. The need for improving the rock bolt drilling and the equipment had to be investigated and the financial implications and justifications for the improved equipment examined. To conduct the search an overall study was done on the rockfalls and safety aspects throughout the platinum industry in South Africa and specifically Union Section. It was found that most of the rock falls in the Merensky stoping areas of which ± 70% are less than 1.2 m in thickness generally occurs within 4 m from the face and causes ± 60% of the in-stope injuries. Serious shortcomings had been identified with respect to the airleg, rock drill machine and the drill steels used in the drilling of the rock bolt holes. Through experimentation, using a testing frame built for this purpose on surface and with the co-operation of mine staff and suppliers, a number of possible modifications were identified and tested. This resulted in the final product with which it was possible to drill a 1.2 m hole in the hangingwall of the stopes ranging with an angle to the hanging from 90° for a 90 cm stoping width and 67° for a 80 cm stoping width. It is confidently concluded that this system will effectively improve the total face support and result in a substantial reduction of rock falls and consequently the occurrence of injuries and fatalities in the Merensky stoping areas. The installation of rock bolts on the face with the modified drilling equipment will increase the direct support, but the system has a potential of a substantial reduction in the profile stick support density and an increase in productivity in the stoping areas due to fewer occurrences of rock falls. It was finally concluded that effective modifications to the drilling equipment for rock bolt in-hole drilling could be made and the installation thereof in the stope face is adequately justified.